ANALISA VIBRASI MAIN SEA WATER PUMP DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN FAILURE MODES AND EFFECT ANALYSIS DI PT KRAKATAU DAYA LISTRIK - Kurniawan, Edi; Gunawan , Wawan; Syarifudin, Achmad (Journal of Industrial Engineering & Management Research, 2020)
Main sea water pump at PLTGU PT. Krakatau Daya Listrik uses sea water as the fluid that flows in it. The examination is carried out to find out what causes the high vibration value, OEE value and RPN value on the Main Sea Water Pump. 29 April 2020 has an alarm status with a value speed of 21.68 mm / s by indicating turbulance or cavitation with a stage alarm. The OEE value for the main sea water pump is 75.61%, with an Availability Value of 95.25%, Performance Efficiency 79.35%, and a Rate of Quality of 100%. Six Big Losses, namely Idle and Minor Stoppage Losses of 54.85%, Reduced Speed Losses of 158%, Equipment Failure Losses of 0%, Setup and Adjustment Losses of 0.08% and for Deffect Losses and Reduced Yeild of 0% which greatly affects the performance of the Main Sea Water Pump, FMEA, the RPN value for each component with the scale of damage (severity), frequency (occurrence), and detection (detection) of the highest RPN Oil Seal, namely 343.The lowest RPN value for the Motor component is 32. The repair plan in this case is to reduce the number of failures or frequencies that occur due to problems with the Main Sea Water Pump, then an improvement plan is carried out, namely the results of the 5W + 1H analysis, checking properly and properly not in a hurry, and training or to improve knowledge for experts, regular service and installation of components correctly when repairs are in accordance with the SOP, and making regular schedules, at carry out regular painting, Understanding of SOP for all operators and giving sanctions to operators who do not follow SOP, Understanding SOP for all operators, especially on operating shifts, and making good repair schedules while carrying out maintenance.